Semiconductor‐to‐Metal Transition and Quasiparticle Renormalization in Doped Graphene Nanoribbons. (10th March 2017) - Senkovskiy, Boris V.; Fedorov, Alexander V.; Haberer, Danny; Farjam, Mani; Simonov, Konstantin A.; Preobrajenski, Alexei B.; Mårtensson, Niels; Atodiresei, Nicolae; Caciuc, Vasile; Blügel, Stefan; Rosch, Achim; Verbitskiy, Nikolay I.; et al.
Abstract : A semiconductor‐to‐metal transition in N = 7 armchair graphene nanoribbons causes drastic changes in its electron and phonon system. By using angle‐resolved photoemission spectroscopy of lithium‐doped graphene nanoribbons, a quasiparticle band gap renormalization from 2.4 to 2.1 eV is observed. Reaching high doping levels (0.05 electrons per atom), it is found that the effective mass of the conduction band carriers increases to a value equal to the free electron mass. This giant increase in the effective mass by doping is a means to enhance the density of states at the Fermi level which can have palpable impact on the transport and optical properties. Electron doping also reduces the Raman intensity by one order of magnitude, and results in relatively small (4 cm −1 ) hardening of the G phonon and softening of the D phonon. This suggests the importance of both lattice expansion and dynamic effects. The present work highlights that doping of a semiconducting 1D system is strikingly different from its 2D or 3D counterparts and introduces doped graphene nanoribbons as a new tunable quantum material with high potential for basic research and applications. Abstract : Graphene nanoribbons are transformed from a semiconductor to a metal by lithium doping. Strong electron doping affects the electronic and optical properties of the material: the quasiparticle band gap is renormalized by ≈0.3 eV and the effective electron mass is increased to the value of free electron. A reduction of the resonance Raman intensity and a phonon energy renormalization are also observed.